Dear friends, Please read our latest blog post for an important announcement about the website. ❤, The Socratic Team

How do you prove #sin^-1(x)+cos^-1(x)=pi/2#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

54
dk_ch Share
Mar 18, 2016

#Let sin^-1x=theta=>x=sintheta=cos(pi/2-theta)#
#=>cos^-1x=pi/2-theta=pi/2-sin^-1x#
#:.sin^-1x+cos^-1x=pi/2#

Was this helpful? Let the contributor know!
1500
Impact of this question
7639 views around the world
You can reuse this answer
Creative Commons License